Long-term persistence of Saliva-derived microRNA in human dental calculus for Forensic investigations - Catia Lippolis; Aldo Cavallini; Ginevra Panzarino; Sandro Sublimi Saponetti (Forensic Science Today - Peertechz Publications, 2019)
Introduction: Human identification is one of the major fields in forensic odontology especially when the dental remains are the only available evidence to individual identification. In this context DNA analysis in teeth pulp remains the most accurate and reliable method for identification, whereas RNA is less used for forensic purpose because it is generally considered a quickly degradable molecule. Recently some studies report that another excellent source of nucleic acids is the dental calculus or tartar. Method: Therefore to assess the RNA stability over time, we investigated 40 saliva-derived microRNAs (miRNAs), in archeological and modern tartar samples by classic PCR followed by quantitative PCR.  Result: Three miRNAs were not present in both ancient and modern tartar samples, while 10 out of 37 miRNAs had significant different levels in ancient than modern samples. Nine miRNAs were down-regulated and only one was up-regulated. Since these different levels were not induced by gum inflammation and were independent to guanine-cytosine content in miRNA sequences, used as degradation biomarker, we hypothesized as a possible cause the different eating habits between ancient and modern populations. This hypothesis is also supported by recent studies that demonstrate an close relationship between nutrients and changes in miRNA expression in healthy individuals. Conclusion: Overall data show that miRNAs are more stable than other RNA types in ancient tartar and this could enlarge the possibility of their practical use for forensic purpose and bioarchaeological researches although to better understand the variability of some miRNA levels between ancient and modern populations requires further investigation.